Mendulang Suara di Masa Pandemi dengan Komunikasi Persuasif (Studi Kasus Pemilihan Umum Kepala Daerah Samarinda Untuk Pasangan Calon dengan Tag Line Siap Dipilih Berani Ditagih) - afita nur hayati (JCommsci - Journal Of Media and Communication Science, 2021)
Direct election’s celebration of the head of the region at each steps in 2020 has been held at pandemic situation of covid-19.  The decision of KPUD Samarinda has final and the candidate number 2 has been sworn with length of service 2021-2024 periods.  The main question that will be asked is how is the candidate number 3 communicates the message they have to be interesting and positively so vote acquisition of the candidat number 3 can align with the candidat number 2 of vote’s acquisition whereas the political machine not so mature than the winner’s political machine. To answer this question, this article uses Analysis of Elaboration Likelihood Model (ELM) and using qualitative descriptive analysis with case study for detail and depth investigation of the candidate number 3 with tag line “Siap Dipilih Berani Ditagih.”